'(S)extremism': Imagining Violent Women in the Twenty-First Century with Navine G. Khan-Dossos and Julia Kristeva. Issue 2 (July 2020) - Downing, Lisa
Abstract : The neologism '(s)extremism' indicates a nexus of ideas intrinsic to the way in which contemporary culture imagines the figure of the violent woman. First, it identifies the sexism visible in reactions to such women; secondly, it highlights the fact that these misogynistic responses are often predicated precisely on sex (i.e. on assumptions about woman's biological function), not (only) on gender ; thirdly, it highlights the question mark that hovers over the issue of what extremism is — especially when applied to women. To examine and theorize these ideas, the article moves beyond existing works in critical terrorism studies and looks to research-informed art installations by international artist Navine G. Khan-Dossos, with whom the author has collaborated, and to the writings of Julia Kristeva who explores the link between female 'extremism' and 'exceptionality', and describes how feminism itself is constituted with regard to the socio-symbolic order as a form of terroristic violence.